FRP Stay in Place Formwork - Goyal, Reema (My University, 2010)
Abstract The new approach for the construction of durable concrete structures is investigated in this research. The aim of this thesis is to develop a novel concept for a hybrid FRP –concrete slab system, in which FRP serves the dual purpose of stay in place formwork when concrete is in wet stage and as reinforcement when concrete has hardened. The system simplifies and accelerates construction and the non corrosive GFRP forms can replace steel rebars, thus negating the problem of steel corrosion when exposed to environment. The purpose of this research was to conduct experimental and analytical studies on the use of GFRP section consisting of GFRP plates stiffened with GFRP channels, as stay in place formwork and reinforcement for concrete slabs. Different GFRP hand lay up sections having different layers of GFRP in plates and channels, different number and arrangement of channels (longitudinal and transverse) are investigated in this work to find out the suitable GFRP section which can satisfy the deflection and strength criteria. 1m long slabs are tested for both wet concrete loading and ultimate strength. 3m long FRP SIP was prepared using connecters which connected three 1m long GFRP forms and were tested for concrete loading to evaluate the performance of connecters. This thesis contains the results of concrete load testing on two single span stiffened double layered forms with and without transverse stiffners. It also includes structural and non structural testing of stiffened four layer forms. Effect of aggregate bonding to the form during structural and non structural testing was studied. One double layered and one four layered three span form was subjected to non structural testing. It was observed that stiffened double layer forms are not suitable for their use as form work. But stiffened four layer forms satisfy both strength and deflection criteria. It was observed that aggregate bond system increases the initial crack load and the ultimate tensile strength. It was concluded that Four layer base form stiffened with four no. four layer channel section can serve the purpose of both formwork and reinforcement.
M.E. (Structural Engineering)
Keywords: FRP, formwork